2013
DOI: 10.1515/cclm-2013-0699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two immunoassays for measurement of faecal calprotectin in detection of inflammatory bowel disease: (pre)-analytical and diagnostic performance characteristics

Abstract: The Thermo Fisher device is not reliable for extraction of faecal calprotectin. The performance characteristics of the EliA Calprotectin assay are statistically equivalent to the Bühlmann POCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 19 publications
2
26
0
4
Order By: Relevance
“…CI, confidence interval; SE, standard error. Along with non-standardisation between the different faecal calprotectin assays, pre-analytical issues of faecal calprotectin analyses can contribute to the (often large) variation in faecal calprotectin concentrations between different assays [6,7,10,26]. In this study, all faecal samples where appropriately homogenised and weighed before extraction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CI, confidence interval; SE, standard error. Along with non-standardisation between the different faecal calprotectin assays, pre-analytical issues of faecal calprotectin analyses can contribute to the (often large) variation in faecal calprotectin concentrations between different assays [6,7,10,26]. In this study, all faecal samples where appropriately homogenised and weighed before extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, faecal calprotectin concentration may be related to inflammation of the bowel mucosa in IBD. Despite some analytical and pre-analytical drawbacks [6][7][8][9][10], encouraging data have recently been published about the clinical efficacy of this biomarker for monitoring disease activity, response to treatment and relapse [11,12]. In addition, faecal calprotectin is resistant to bacterial degradation, being stable in stool for up to 3 days at room temperature, which adds more benefits to its use as a laboratory marker [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of eight studies totaling 1062 subjects recently concluded that a patient with a fecal calprotectin value ≤ 40 μg/g has a 1% probability of having IBD and a 84.1% probability of being healthy [5], thus exhibiting better diagnostic performance than C-reactive protein, erythrocyte sedimentation rate and fecal lactoferrin for ruling out this condition. Despite some analytical and preanalytical drawbacks remain [6][7][8][9], encouraging data has also been recently published about the clinical efficacy of this biomarker for monitoring disease activity, response to treatment and relapse [10,11].…”
mentioning
confidence: 99%